2007
DOI: 10.2174/092986707781745541
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic Endothelial Cells, Inflammatory Lymphangiogenesis, and Prospective Players

Abstract: De novo lymphangiogenesis influences different pathological courses via modulating tissue fluid homeostasis, macromolecule absorption, and leukocyte transmigration. During the past decade, improved understanding of lymphatic biology, especially VEGF-C/-D/VEGFR-3-mediating lymphangiogenesis has substantially promoted clinical research in lymphatic insufficiency. The role of lymphangiogenesis in the setting of the inflammatory processes observed in transplants, inflamed cornea, wound healing, acquired lymphedema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 115 publications
(153 reference statements)
0
38
0
Order By: Relevance
“…Although several studies have shown the close association of inflammation and lymphangiogenesis (19,46,47,64), the role of the proinflammatory cytokine TNF-␣ in modulating lymphangiogenesis remains controversial (4,6,22,48). Since miR-9 was upregulated in the TNF-␣-treated LECs and it also directly targets NF-B, we assessed the effects of miR-9 in LECs on lymphatic tube formation.…”
Section: Mir-9 Inhibits Nf-b Signaling In Lecs But Promotes Lymphaticmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several studies have shown the close association of inflammation and lymphangiogenesis (19,46,47,64), the role of the proinflammatory cytokine TNF-␣ in modulating lymphangiogenesis remains controversial (4,6,22,48). Since miR-9 was upregulated in the TNF-␣-treated LECs and it also directly targets NF-B, we assessed the effects of miR-9 in LECs on lymphatic tube formation.…”
Section: Mir-9 Inhibits Nf-b Signaling In Lecs But Promotes Lymphaticmentioning
confidence: 99%
“…Lymphatic endothelial cells (LECs) at a site of inflammation have been shown to actively participate in and regulate inflammatory processes and host immune responses, thereby emerging as major players in progression and resolution of the inflammatory state (18,19,46,47,50,64). Since inflammation acts as a primary trigger for pathological lymphangiogenesis, a number of proinflammatory cytokines have also been shown to function as prolymphangiogenic factors (15,25,49).…”
mentioning
confidence: 99%
“…LECs may, additionally, undergo similar cellular processes like proliferation, differentiation, and formation of new networks. In the past decade, lymphangiogenesis including its molecular and functional characteristics, and macrophages including their alternative activation in tumor and inflammation have been reviewed separately [9,[12][13][14][15]. The role of macrophages in the formation of new initial lymphatics remains to be elucidated.…”
Section: Bmdcsmentioning
confidence: 99%
“…Adult lymphangiogenesis occurs during inflammation and wound healing [1,10], but is also strongly associated with chronic inflammation, autoimmunity, and allograft rejection [11][12][13][14][15][16] as well as with tumor invasion and metastasis when initiated both around the tumor and in the draining LN [17][18][19][20][21]. These are all associated with different immunological outcomes: from Th1 and Th2 inflammatory responses to immune escape and tolerance.…”
Section: Introductionmentioning
confidence: 99%